Analysis of Adjective Clauses in John Steinbeck’s Novel “Of Mice and Men” - Budi Awan Marpaung; Deliana Deliana (LPPM Universitas Bumigora Mataram, 2024)
The study's main purpose is to describe the types of adjective clauses. The method of this study was a descriptive qualitative method that focused on describing the types of adjective clauses. The method of data collection is by using the documentation method. The technique is collecting complex sentences that are found in the novel. There were some steps to do this analysis such as reading several textbooks and articles about English grammar, and seeking and learning information about adjective clauses, definitions, the types of adjective clauses, and then identifying and classifying the data of English adjective clauses in John Steinbeck’s novel Of Mice and Men. Next, the data based on the types of adjective clauses were analyzed and then showed the frequency of types from each act of data in the novel, and finally drawing verification conclusions after finishing the analysis. King and Stanley (1996) describe that types of adjective clauses can be divided into four, they are full adjective clause, reduced adjective clause, marked adjective clause, and unmarked adjective clause. The result shows there were only two types of adjective clauses in the novel, 48 full adjective clauses equal to 98 percent, and 1 reduced adjective clause clauses equal to 2 percent. It is concluded that almost all types of adjective clauses are full adjective clauses in John Steinbeck’s novel Of Mice and Men. It means that the way the writer delivers conversation and narration on the text with full adjective clauses is to make it easier for readers to understand them.